Arterial wall thickness and blood pressure in children who were born small for gestational age: correlation with umbilical cord high-sensitivity C-reactive protein. Issue 1 (21st September 2009) - Trevisanuto, D; Avezzù, F; Cavallin, F; Doglioni, N; Marzolo, M; Verlato, F; Zanardo, V
Abstract : Background: Small for gestational age (SGA) infants have an increased risk of later cardiovascular disease. At birth, high sensitivity-C reactive protein (hs-CRP), a prognostic marker of cardiovascular disease, is significantly higher in SGA than in appropriate for gestational age (AGA) infants. Aim: To measure aortic and carotid intima-media thickness (aIMT, cIMT) and blood pressure (BP) in children (aged 3–5 years) who were born SGA and AGA, and to assess the correlation between hs-CRP concentrations obtained at birth and these haemodynamic variables. Methods: Umbilical cord hs-CRP concentrations were obtained in 38 neonates. In the same subjects aged 3–5 years, aIMT and cIMT were measured by high-resolution ultrasound scan, in the dorsal arterial wall. Anthropometric variables and BPs were obtained for each child. Results: Maximum (median 0.700 mm, range 0.500–1.080 vs 0.650 mm, 0.400–0.860; p = 0.32) aIMTs were similar between children who were born SGA (n = 17) and AGA (n = 21), respectively. Concentrations of hs-CRP were not correlated with IMTs. In children who were born SGA, systolic BP was significantly correlated with umbilical cord hs-CRP concentrations (r = 0.60; p = 0.009). Conclusions: Children who were born SGA have a higher, although not significant, aortic thickening than those who were born AGA. Umbilical cord hs-CRP concentrations do not seem to be involved in this process. Instead, hs-CRP concentrations were significantly related to systolic BP values in children who were born SGA, suggesting that hs-CRP at birth could be associated with sympathetic system hyperactivity and with the stress response during childhood.